Proceedings of the First Workshop on Self-Healing Systems 2002
DOI: 10.1145/582128.582138
|View full text |Cite
|
Sign up to set email alerts
|

Architectural style requirements for self-healing systems

Abstract: This paper argues for a set of requirements that an architectural style for self-healing systems should satisfy: adaptability, dynamicity, awareness, autonomy, robustness, distributability, mobility, and traceability. Support for these requirements is discussed along five dimensions we have identified as distinguishing characteristics of architectural styles: external structure, topology rules, behavior, interaction, and data flow. As an illustration, these requirements are used to assess an existing architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…More generally, to achieve self-healing in software systems, an architectural style needs to meet certain requirements [85], which include adaptability, dynamicity, awareness, autonomy, robustness, distributability, mobility and traceability. These requirements support the four phases of a self-adaptive software life cycle which consists of monitoring, planning the necessary changes, deploying change descriptions and enacting the changes.…”
Section: Surveymentioning
confidence: 99%
“…More generally, to achieve self-healing in software systems, an architectural style needs to meet certain requirements [85], which include adaptability, dynamicity, awareness, autonomy, robustness, distributability, mobility and traceability. These requirements support the four phases of a self-adaptive software life cycle which consists of monitoring, planning the necessary changes, deploying change descriptions and enacting the changes.…”
Section: Surveymentioning
confidence: 99%
“…Prism-MW uses a set of core classes to represent the basic architectural elements: Architecture, Component, Connector, and Port. It also provides an explicit extension mechanism (via Java's abstract classes and interfaces) to implement specific variants of these elements for use in different application scenarios and architectural styles [8,7]. We use Prism-MW, and rely particularly on its extensibility mechanisms and native support for architectural styles, in our approach as discussed below.…”
Section: Related Workmentioning
confidence: 99%
“…Research carried out over the past decade has demonstrated that software architectures can be particularly effective in this capacity [14,16,27].Architectures provide a high-level view of the system, reducing the complexity of understanding what the system is doing, and supporting scalability to complex distributed systems. Suitably annotated architectures also permit the autonomic decision-making apparatus to detect the presence of systemic problems and trends, such as degraded performance.…”
Section: Introductionmentioning
confidence: 99%